Effect of flip angle on the accuracy and repeatability of hepatic proton density fat fraction estimation by complex data‐based, T1‐independent, T2*‐corrected, spectrum‐modeled MRI. Issue 2 (17th April 2013) - Johnson, Benjamin L.; Schroeder, Michael E.; Wolfson, Tanya; Gamst, Anthony C.; Hamilton, Gavin; Shiehmorteza, Masoud; Loomba, Rohit; Schwimmer, Jeffrey B.; Reeder, Scott; Middleton, Michael S.; Sirlin, Claude B.
Abstract : Purpose: To evaluate the effect of flip angle (FA) on accuracy and within‐examination repeatability of hepatic proton‐density fat fraction (PDFF) estimation with complex data‐based magnetic resonance imaging (MRI). Materials and Methods: PDFF was estimated at 3T in 30 subjects using two sets of five MRI sequences with FA from 1° to 5° in each set. One set used 7 msec repetition time and acquired 6 echoes (TR7/E6); the other used 14 msec and acquired 12 echoes (TR14/E12). For each FA in both sets the accuracy of MRI‐PDFF was assessed relative to MR spectroscopy (MRS)‐PDFF using four regression parameters (slope, intercept, average bias, R 2 ). Each subject had four random sequences repeated; within‐examination repeatability of MRI‐PDFF for each FA was assessed with intraclass correlation coefficient (ICC). Pairwise comparisons were made using bootstrap‐based tests. Results: Most FAs provided high MRI‐PDFF estimation accuracy (intercept range −1.25 to 0.84, slope 0.89–1.06, average bias 0.24–1.65, R 2 0.85–0.97). Most comparisons of regression parameters between FAs were not significant. Informally, in the TR7/E6 set, FAs of 2° and 3° provided the highest accuracy, while FAs of 1° and 5° provided the lowest. In the TR14/E12 set, accuracy parameters did not differ consistently between FAs. FAs in both sets provided high within‐examination repeatability (ICC range 0.981–0.998). Conclusion: MRI‐PDFF was repeatable and, for most FAs, accurate in both sequence sets. In the TR7/E6 sequence set, FAs of 2° and 3° informally provided the highest accuracy. In the TR14/E12 sequence set, all FAs provided similar accuracy.J. Magn. Reson. Imaging 2014;39:440–447 . ©2013 Wiley Periodicals, Inc .